Projections of Climate Change Impact on Acute Heat Illnesses in Taiwan: Case-Crossover Study - Hsiao-Yu Yang; Chang-Fu Wu; Kun-Hsien Tsai (JMIR Public Health and Surveillance)
Abstract BackgroundWith global warming, the number of days with extreme heat is expected to increase and may cause more acute heat illnesses. While decreasing emissions may mitigate the climate impacts, its effectiveness in reducing acute heat illnesses remains uncertain. Taiwan has established a real-time epidemic surveillance and early warning system to monitor acute heat illnesses since January 1, 2011. Predicting the number of acute heat illnesses requires forecasting temperature changes that are influenced by adaptation policies. ObjectiveThe aim of this study was to estimate the changes in the number of acute heat illnesses under different adaptation policies. MethodsWe obtained the numbers of acute heat illnesses in Taiwan from January 2011 to July 2023 using emergency department visit data from the real-time epidemic surveillance and early warning system. We used segmented linear regression to identify the join point as a nonoptimal temperature threshold. We projected the temperature distribution and excess acute heat illnesses through the end of the century when Taiwan adopts the “Sustainability (shared socioeconomic pathways 1‐2.6 [SSP1-2.6]),” “Middle of the road (SSP2-4.5),” “Regional rivalry (SSP3-7.0),” and “Fossil-fueled development (SSP5-8.5)” scenarios. Distributed lag nonlinear models were used to analyze the attributable number (AN) and attributable fraction (AF) of acute heat illnesses caused by nonoptimal temperature. ResultsWe enrolled a total of 28,661 patients with a mean age of 44.5 (SD 15.3) years up to July 2023, of whom 21,619 (75.4%) were male patients. The nonoptimal temperature was 27 °C. The relative risk of acute heat illnesses with a 1-degree increase in mean temperature was 1.71 (95% CI 1.63-1.79). In the SSP5-8.5 worst-case scenario, the mean temperature was projected to rise by +5.8 °C (SD 0.26), with the AN and AF of acute heat illnesses above nonoptimal temperature being 19,021 (95% CI 2249‐35,792) and 89.9% (95% CI 89.3%‐90.5%) by 2090‐2099. However, if Taiwan adopts the Sustainability SSP1-2.6 scenario, the AN and AF of acute heat illnesses due to nonoptimal temperature will be reduced to 12,468 (95% CI 3233‐21,704) and 62.1% (95% CI 61.2‐63.1). ConclusionsAdopting sustainable development policies can help mitigate the risk of acute heat illnesses caused by global warming.